PEMODELAN SPASIAL KESESUAIAN HABITAT ELANG JAWA (Nisaetus bartelsi Stresemann, 1924) DI TAMAN NASIONAL GUNUNG HALIMUN-SALAK - Andi N. Cahyana; Jarwadi B. Hernowo; Lilik Budi Prasetyo (Media Konservasi, 2015)
Javan hawk-eagle (Nisaetus bartelsi) is an endemic raptor species which has limited distribution area in Java Island. Their existence is threatened (endangered) due to their small population, habitat degradation as well as fragmentation. Gunung Halimun Salak National Park (GHSNP) is known for having the highest population of javan hawk-eagle. We conducted habitat suitability modeling of javan hawk-eagle in the GHSNP using principal component analysis (PCA) scoring method with 10 habitat variables, i.e.: altitude, slope, aspect, forest canopy density (FCD), temperature, rainfall, river distribution, road distribution, settlement distribution and population density. The results of this study showed that from total study area, 94,43% of high suitable habitat for javan hawk-eagle contained in GHSNP area. It means that the GHSNP is very important area for the existence and the conservation of the javan hawk-eagle population.The highly suitable class of javan hawk-eagle habitat is distributed on the areas with an average value for each habitat variable as follows: 68,96±11,18% (for FCD), 3.883,05±299,61 mm/year (rainfall), 19,93±1,72 ºC (temperature), 1.136,05±271,46 masl (altitude), 2.207,69±1.445,86 m (distance from road), 2.727,51±1.554,61 m (distance from settlement) and 3.829,08±1.504,37 individual (population density). The habitat suitability model resulted from this research can be used as a reference in identifying priority areas for better habitat management of javan hawk-eagle in the GHSNP. Keywords: Gunung Halimun Salak National Park, habitat suitability, Javan Eagle-hawk, spatial model